Implementation of Parenting Programs and Its Impact on Parents' Participation in Aisyiyah Pancor Integrated PAUD - Mahsur, Mahsur; Wildan, Wildan; Baehaqi, Baehaqi (Balai Publikasi Indonesia, 2024)
The purpose of this qualitative research is to describe the planning, implementation, evaluation and impact of parenting programs conducted by school principals, teachers and committees of Aisyiyah Pancor Integrated PAUD on parent participation. The research approach used is a qualitative approach using descriptive methods. The survey was conducted at PAUD Terpadu Aisyiyah Pancor, Selong District. The researcher and the resource person have the same position here, therefore the resource person not only provides an answer to what the researcher is asking, but he can choose the direction and taste in presenting the information he has. The data collected through interviews (interviews), observation (observation) and documentation (evidence collection, selection, processing and information storage). The data collection techniques used were in-depth interviews, observation and documentation. The data validity test in this study includes test, credibility (interbal validity), transferability (external validity) and reliability (reliability) and confirmability (objectivity). The results showed that the implementation of planning, implementation and evaluation of parenting programs in PAUD Terpadu Aisyiyah Pancor went well. The impact of the parenting program is to be able to stimulate parental participation, applying different behaviors of children in the daily life seen from different aspects, such as education-friendly, health-friendly, care-friendly, care-friendly, food-friendly and protection-friendly, causing a change the parental behavior occurs in the education, care, care and supervision of children in the family